THE INFLUENCE OF KNOWLEDGE AND MOTIVATION ON NURSE BEHAVIOR IN THE IMPLEMENTATION OF PATIENT SAFETY AT BHAYANGKARA BRIMOB HOSPITAL DEPOK - Saumadin Saumadin; Ajeng Tias Endarti; Siti Jumhati; Arinando Pratama (SOSIOEDUKASI, 2026)
Patient Safety is a key indicator of hospital service quality, requiring the implementation of operational standards and a safety culture. At Bhayangkara Brimob Hospital, Depok, high rates of Patient Safety incidents, nurses' lack of understanding of safety procedures, and low work motivation are still found, which impact compliance with the Patient Safety program. To analyze the influence of knowledge and motivation on nurses' behavior in implementing Patient Safety at Bhayangkara Brimob Hospital, Depok. This research used a quantitative method with a cross-sectional design. This study was conducted on 78 nurses at Bhayangkara Brimob Hospital, Depok. Unvariate, bivariate, and multivariate analysis were used. The results of the bivariate analysis using the chi-square test showed that nurses’ demographic characteristics (age, gender, education level, and years of service) did not have a significant effect on nurses’ behavior in implementing Patient Safety (p>0.05). Meanwhile, knowledge (p=0.000; OR=7.677) and motivation (p=0.000; OR=7.770) had a significant effect on nurses’ behavior in implementing Patient Safety. Stress management also showed a significant association (p=0.000; OR=5.762); however, in the multivariate analysis it was positioned as a control variable. The results of logistic regression analysis indicated that knowledge and motivation remained significantly associated with nurses’ behavior in implementing Patient Safety after being controlled by stress management. The Nagelkerke R² value of 0.495 indicates that approximately 49.5% of the variation in nurses’ Patient Safety behavior can be explained by knowledge and motivation after considering the controlling factor. Bhayangkara Brimob Hospital Depok needs to improve nurses’ competence and motivation through regular training, case-based workshops, as well as continuous supervision and mentoring. In addition, strengthening organizational support, including stress management programs and reward systems, can be implemented as supporting strategies to enhance compliance with Patient Safety principles